The Effect of Belly Binding and Abdomen Exercise on Reducing Diastasis Recti Abdominis in Postpartum Mothers - Sophia Sophia; Fitri Nurhayati; Rika Nurhasanah (STIKep PPNI Jawa Barat, 2023)
Aims : The purpose of this study was to see if belly binding and abdominal exercises may help reduce diastasis recti abdominis in postpartum women. Methods : A quasi experiment with a One group Pretest Posttest Design was employed as the research approach. Respondents were 60 primiparous postpartum moms who were randomly assigned to one of two groups: 30 for belly binding treatment and 30 for abdominal exercises treatment, using the purposive sample technique. Results : The findings revealed that belly binding had an influence on the decrease in DRA in postpartum women (p value = 0.000). Abdominal exercises had a positive effect on DRA in postpartum women (p value = 0.043). It is recommended that postpartum women employ belly binding and abdominal workouts to combat DRA. Conclusion : Belly binding and abdominal exercises can help postpartum women overcome recti abdominis. Midwives are supposed to be able to give passive and active non-pharmacological midwifery treatment, such as belly bindings and abdominal exercises for postpartum women suffering from DRA.